Eksistensi Nilai-nilai Ilahiah dalam Fisika SMA di Aceh - Nur'aini Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
High school physics is strongly influenced by the philosophy of materialism and positivism, that the universe has no relation with the transcendent and metaphysical, universe happen by itself no divine intervention, there is not even that it creates. Though the universe is physical evidence of the existence of Allah as the Creator. The purpose of this study was to describe (1) The existence of divine values in high school physics, (2) the omnipotence of divine values in high school physics, and (3) the values of divine perfection in high school physics. The approach taken in this study is a qualitative approach. Determination of informants based on consideration of engagement, at eight high schools in Aceh and Aceh stakeholders. Data collection techniques used in this study were (1) interview, (2) observation, and (3) study the documentation. For that data obtained from informants and analyzed by the reduction, data presentation and conclude. The findings showed that (1) God the Creator has created the planets in the universe each outstanding in orbit, such as the sun, the moon, the animals, the earth / sky. He has created energy such as the sun, moon, stars, wind, metal, sound, motion, electricity and water, (2) Allah the Almighty is able to predetermine each planet circulating in orbit such as the sun, moon, stars, earth / sky. He has been in power predetermine a variety of energy, such as sun, moon, stars, wind, metal, motion, sound, electricity and water. (3) Allah the almighty One has created beings in pairs, like the sun and the moon, sun and earth / sky, earth and sky, night and day, stamens and pistils, male and female, man and woman, husband and wife, Muslims and non-Muslims and secular each has a set of characteristics. The almighty Allah Almighty has created all the energy, like the sun, moon, stars, wind, metal, motion, electricity and water as a human living facilities to serve Allah.